Evidence of hydrophobic interactions controlling mobile ions release from smart hydrogels - Molina, María Alejandra (2010)
A water soluble cationic metal complex (tris(2,2'-bipyridine)ruthenium(II)) can be loaded into hydrogels containing acrylamide and/or acrylic acid units. The cationic complex is retained in polymer containing acrylic acid units at high pH and released at low pH. This is likely due to electrostatic interactions of the cation with the carboxylate anions, present at high pH, which are converted into neutral carboxylic acid at low pH, releasing the metal complex. Since the gel contract at low pH, the water soluble cation is also released with the water expelled from the gel. However, a strong retention of the cation inside the gels is observed when acrylamide units are present. A possible explanation is a hydrophobic interaction of the large metal complex with the polyacrylamide network. Using the counteracting electrostatic and hydrophobic interactions of probe molecules with smart hydrogel matrixes it is possible to tune the pH of maximum release away from the pKa of the ionizable group.